Exploring Modern Islamic Boarding School English Textbooks Based on the SLA Principles - Saputri, Avida Pramayshela (Journal of English Language Teaching and Cultural Studies, 2025)
The main focus of this study is to analyze the activity in the "English Lesson" textbook utilized in contemporary Islamic boarding schools, which is published by Gontor Press. The researcher's objective was to conduct a thorough analysis of the English lesson book designed for sixth-grade students. In modern Islamic boarding schools, the sixth grade corresponds to the third grade in senior high school. This article employs qualitative research methods, specifically concentrating on content analysis proposed by Littlejohn (2011) regarding three main questions: What is the learner supposed to achieve? With whom? What material? Each question describes certain criteria that outline the elements of the three questions to describe the textbook material. Additionally, the author employs the idea of the ten principles of SLA proposed by Ellis (2005) to enhance the task-based analysis presented in the textbook. Findings indicate that vocabulary-based and sentence-building tasks have the potential to support L2 acquisition by providing both explicit and implicit knowledge. However, the analysis identifies a limited presence of interactive and communicative tasks. This research serves as a preliminary step before evaluating and highlighting the importance of SLA principles in designing effective English textbooks for Islamic boarding schools. This research can be used to increase the awareness of EFL teachers, English textbook material makers, and English textbook policymakers about the importance of SLA principles in textbook materials that can help students master English.